2007
DOI: 10.1590/s1415-54192007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Expansão rápida da maxila ancorada em implantes: uma nova proposta para expansão ortopédica na dentadura permanente

Abstract: OBJETIVO: este trabalho apresenta um método para expansão ortopédica da maxila, na dentadura permanente, utilizando implantes como ancoragem. METODOLOGIA: detalharam-se os procedimentos cirúrgicos e laboratoriais da confecção de um expansor com ancoragem dento-óssea em crânio seco humano. Dois implantes de titânio foram colocados na região anterior do palato, e o parafuso Hyrax adaptado de modo que a expansão ancorou-se nos implantes e nos primeiros molares permanentes. RESULTADOS: o experimento laboratorial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
5
Order By: Relevance
“…Regarding the limitations of MARPE devices, Garib et al reported that MARPE therapy requires a longer activation time and twice the force for the rupture of the medial palatine suture compared to SARPE [25]. Other disadvantages of MARPE: it may cause temporary inflammation of the palatal mucosa [26], difficulty in hygiene around micro-implants, and risk of infection [1].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the limitations of MARPE devices, Garib et al reported that MARPE therapy requires a longer activation time and twice the force for the rupture of the medial palatine suture compared to SARPE [25]. Other disadvantages of MARPE: it may cause temporary inflammation of the palatal mucosa [26], difficulty in hygiene around micro-implants, and risk of infection [1].…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki 2019Um outro fator observado que favorece a abordagem de expansão com corticoperfurações das cristas infrazigomáticas é o de minimizar as possíveis instabilidades dos miniparafusos, quando ativados independente do protocolo utilizado e as movimentações vestibulares dos dentes ancorados. Garib (2007) Mesmo sabendo que as áreas de maior dissipação de força durante as ativações do expansor, continuam sendo a placa bucal dos dentes ancorados e do processo frontal do osso maxilar e não a área da sutura palatino Seong (2017), a melhor distribuição das forças com o uso dos parafusos de fixação do expansor e a menor resistência ao deslocamento lateral na região das cristas zigomáticas, diminuem a tensão sobre essas áreas o que normalmente causa certa preocupação.…”
Section: Discussionunclassified
“…O procedimento de expansão rápida da maxila (ERM) tem como principal finalidade a correção da atresia do arco dentário pela abertura da sutura intermaxilar e consequente incremento transversal da base óssea superior. Garib (2007) Considerando a necessidade de mesmo antes das cimentações do aparelho MARPE já serem feitas as corticoperfurações ao longo da rafe palatina, a anestesia local deve ser iniciada Research, Society and Development, v. 9, n. 10, e7589108414, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8414 de anterior para posterior nos locais de perfurações, para assim durante as aplicações o líquido anestésico ir se dissipando para trás, fazendo com que apenas a primeira introdução da agulha seja percebida.…”
Section: Relato De Casounclassified
“…MARPE benefits and advantages reported in the literature are described as follows: minimal dental inclination [1, 37, 38]; less risk of damaging effects to the periodontium such as gingival retraction and root resorption [2, 37]; greater vertical control in dolichofacial patients [1]; reduction of tooth movement of anchor teeth [5]; increased protraction of the maxilla when associated to facemask therapy [39]; indicated to patients at the end of the growth and adults [6, 10]; avoidance of orthognathic surgery[5]; stability of the expansion and decrease of relapse [2, 6]; forces applied directly to the midpalatal suture and less amount of force applied to the teeth [40]; and airway improvement [5]. The results of this case report showed that it is possible to correct maxillary constriction in an adult patient using a MARPE appliance which promoted more skeletal effects such as midpalatal suture split and an increase in the basal bone and cortical bone widths than dental tipping, avoiding SARPE procedure in a period of 20 days of activations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Garib et al reported that the MARPE method presented the disadvantage of requiring a longer activation time and twice the force for the rupture of the medial palatine suture compared to SARPE [37]. Other disadvantages are related to the following: it may cause temporary inflammation of the palatal mucosa [2], difficulty in hygiene around microimplants, and risk of infection [1].…”
Section: Discussionmentioning
confidence: 99%